Power quality improvement using a shunt active power filter based on an cascaded H-bridge eleven level inverter with predictive current control - Abdelkader, Yousfi; Chaker, Abdelkader; Bot, Youcef (International Journal of Applied Power Engineering (IJAPE), 2021)
The active power filter has proven to be an effective method for attenuating harmonic currents generated by non-linear loads as well as for compensating reactive power. This paper presents a comparison study between two control methods associated with a shunt active power filter based on eleven-level type cascaded inverter. The first method is based on the conventional PI regulator and the second is based on the predictive current controller. The eleven-level type cascade inverter has more advantages relatively to the two-level inverter; among them: better total harmonic distortion, reduced semiconductor switches ratings and reduced switching losses. The performance of the APF is tested by simulation using Matlab/Simulink. The predictive controlled the APF associated with the multi-level inverter shows more performances and efficiency compared to the conventional control algorithms.